2013
DOI: 10.4103/2230-8210.111677
|View full text |Cite
|
Sign up to set email alerts
|

False positive results using calcitonin as a screening method for medullary thyroid carcinoma

Abstract: The role of serum calcitonin as part of the evaluation of thyroid nodules has been widely discussed in literature. However there still is no consensus of measurement of calcitonin in the initial evaluation of a patient with thyroid nodule. Problems concerning cost-benefit, lab methods, false positive and low prevalence of medullary thyroid carcinoma (MTC) are factors that limit this approach. We have illustrated two cases where serum calcitonin was used in the evaluation of thyroid nodule and rates proved to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Follicular and papillary thyroid carcinomas could also be associated with CCH and slightly high calcitonin levels (70,71). Cases have also been reported of benign multinodular goiter with false positive calcitonin associated with neither CCH nor MTC in surgical specimens (72,73). Discordant data are reported for chronic autoimmune thyroiditis (74,75,76).…”
Section: False Positives and False Negativesmentioning
confidence: 94%
“…Follicular and papillary thyroid carcinomas could also be associated with CCH and slightly high calcitonin levels (70,71). Cases have also been reported of benign multinodular goiter with false positive calcitonin associated with neither CCH nor MTC in surgical specimens (72,73). Discordant data are reported for chronic autoimmune thyroiditis (74,75,76).…”
Section: False Positives and False Negativesmentioning
confidence: 94%
“…1 Calcitonin (CT) production is a characteristic feature of this tumor. However, several technical factors can affect the CT assay, and other nonthyroidal pathologic conditions can increase CT, 2,3 thus limiting its routine use in clinical practice. The American Thyroid Association (ATA) task force has confirmed that they could not make recommendations for or against the routine measurement of CT. 4 Furthermore, the American Association of Clinical Endocrinologists/Associazione Medici Endocrinologi/European Thyroid Association (AACE/AME/ ETA) guidelines have suggested examining CT only in subjects with a familial history of MTC and patients with cytology suggestive of MTC or undergoing surgery for goiter.…”
Section: Introductionmentioning
confidence: 99%
“…Calcitonin (CT) production is a characteristic feature of this tumor. However, several technical factors can affect the CT assay, and other nonthyroidal pathologic conditions can increase CT, 2,3 thus limiting its routine use in clinical practice. The American Thyroid Association (ATA) task force has confirmed that they could not make recommendations for or against the routine measurement of CT 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, false positives may occur frequently in both basal and stimulated measurements of calcitonin [ 6 ]. Benign pathologies causing an increase in calcitonin levels include benign hyperplasia of C cells, benign thyroid nodules, differentiated thyroid carcinoma and Hashimoto thyroiditis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%